Clonagem, expressão e caracterização de um inibidor de tripsina presente no mosquito Aedes aegypti - Watanabe, Renata Midori Okuta [UNIFESP] (2010)
The Aedes aegypti mosquito is the classic vector of yellow fever and dengue fever. In haematophagous insects, blood digestion is carried out by proteolitic enzymes, which can also be envolved in parasite-vector relationship. Blood feeding requires that haematophagous insects are able to inhibit host hemostatic defenses, containing inhibitors of coagulation cascade enzymes, for example. In order to understand the vector bilogy, the aim of this work was expression and characterization of a Kazal-type serine protease inhibitor present in Aedes aegypti mosquito. Recombinant inhibitor (rAaTI) and its truncated form rAaTIΔ (without Cterminal region) were expressed in Pichia pastoris system and purified by affinity chromatography. Purified rAaTI was able to inhibit amidolytic activity of trypsin, plasmin and weakly inhibited thrombin. rAaTI was also able to prolong coagulation time, and there are evidences that inhibitor bind in some region occupied by heparin or antithrombin III. Transcription analyzes showed that AaTI is present in salivary gland and midgut of females 3 and 24 h after blood feeding, and in all larval instars, pupae and males, which suggest that inhibitor may have other functions in mosquito development. rAaTI was also able to strongly inhibit trypsin from 4th instar lavae , and female trypsin 3 and 34 h after blood feeding, suggesting that rAaTI may be involved in trypsin modulation in larval phase and in the end of blood difgestion.